2008
DOI: 10.1128/jb.01009-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bdellovibrio bacteriovorus HD100 Bd0714 as a Nudix dGTPase

Abstract: Bdellovibrio bacteriovorus bacteria are predatory organisms that attack other gram-negative bacteria. Here, we report that Bd0714 is a Nudix dGTPase from B. bacteriovorus HD100 with a substrate specificity similar to that of Escherichia coli MutT and complements an E. coli mutT-deficient strain. We observed different transcription levels of the gene throughout the predator life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(12 reference statements)
2
14
0
Order By: Relevance
“…Pineiro and co-workers [43] mutagenised a Bdellovibrio nudix hydrolase gene Bd0714 but found that it had no effect upon the predatory growth of the bacteria, our studies support this showing that in comparison to attack-phase growth Bd0714 was up-regulated in HI growth, but showed no change in expression at 30 minutes post-predation.…”
Section: Resultssupporting
confidence: 75%
“…Pineiro and co-workers [43] mutagenised a Bdellovibrio nudix hydrolase gene Bd0714 but found that it had no effect upon the predatory growth of the bacteria, our studies support this showing that in comparison to attack-phase growth Bd0714 was up-regulated in HI growth, but showed no change in expression at 30 minutes post-predation.…”
Section: Resultssupporting
confidence: 75%
“…RT-PCR analyses carried out on RNA samples taken at intervals from synchronous B. bacteriovorus infections were used to monitor the expression of mreB1/mreB2 and mreCD. The RT-PCR had the number of amplification steps limited, so as not proceed to saturation and can therefore be used as a semiquantitative measure of gene expression across a B. bacteriovorus infection cycle, as confirmed previously in comparison to quantitative RT-PCR (10,34). Multiple sets of reactions on a minimum of two independently prepared RNA sample sets are summarized in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In summary, 8-oxo-dGMP is surrounded by 12 types of hydrogen bonds. The hydrogen-bonding interactions with the pyrimidine moiety and the ␣-phosphate group in MutT-8-oxo-dGMP are similar to those with the corresponding pyrimidine moieties and ␣-phosphate groups in the structures of BdRppH-GTP-Mg 2ϩ and BdRppH-dGTP (BdRppH- (7,44). This may derive from these structural differences, in addition to the unfavorable syn conformation of (d)GTPs in BdRppH-(d)GTPs.…”
Section: Resultsmentioning
confidence: 92%